Evaluation of thickness estimation techniques in seismically thin beds - Valentina Ortiz Bustos; Rodrigo Abarca-del-Río; Arturo Belmonte-Pool; Matthew Miller (My University, 2020)
The quantitative estimation of rock strata thickness below the vertical seismic resolution limit is a great challenge for seismic exploration. Most previous studies are focused on thin layers interspersed within an infinite homogeneous rock which does not exhibit interference effects due to the presence of other rock strata. These cases are not representative of most real-life situations, so their results cannot be considered to be general. In this paper we experimentally evaluate the use of the peak instantaneous frequency, dominant frequency, and spectral decomposition attributes in the quantification of thin layers by using two simple isolated-layer wedge models and a third multilayer wedge model which simulates a stratified formation. We conclude that, in the presence of interference, only spectral decomposition would allow us to estimate the thickness of a thin layer, and even the thicker ones. However, its relationship with layer thickness is inverted when varying the elastic properties of the formation under evaluation, so this attribute should only be used in rock strata whose elastic properties remain approximately constant.
Keywords: Wedge (geometry)